The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.2110/palo.2010.p10-140r
|View full text |Cite
|
Sign up to set email alerts
|

A Surrogate Approach to Studying the Chemical Reactivity of Burrow Mucous Linings in Marine Sediments

Abstract: Many infaunal marine invertebrates produce mucous excretions, composed primarily of the glycoprotein mucin, that play important roles in burrow stabilization. As with other biopolymers, the ionization of mucin provides highly reactive organic ligands that enable the sorption of metal cations from seawater. Owing to the difficulties in its isolation, however, the specific role of mucin in the adsorptive properties of animal secretions in marine environments is poorly understood. Here we apply a surface complexa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 44 publications
(60 reference statements)
0
22
0
Order By: Relevance
“…Mucus secretions were observed in the burrow walls of the polychaete treatments. Considering that polychaete mucus has a considerable buffering capability [32], it is likely that these secretions are responsible for the increase in seawater pH (Figure 4). The mucus secretions are used to trap and accumulate organic detritus from the water column during filter feeding as fresh seawater is pumped through the burrow [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mucus secretions were observed in the burrow walls of the polychaete treatments. Considering that polychaete mucus has a considerable buffering capability [32], it is likely that these secretions are responsible for the increase in seawater pH (Figure 4). The mucus secretions are used to trap and accumulate organic detritus from the water column during filter feeding as fresh seawater is pumped through the burrow [33].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we have 3 explanations for the greater concentrations of labile Hg(II) in the walls of worm burrow samples in both the Wolfville and Windsor sediments (Figure 2). The labile Hg(II) may be 1) a chemical constituent of polychaete mucus secretions or the organic detritus trapped by worm mucus, 2) bound to sites on the surface of the organic detritus [37] or deprotonated functional groups on mucus glycoproteins [32], or 3) assimilated by bacteria feeding on the detritus and mucus secretions.…”
Section: Discussionmentioning
confidence: 99%
“…Size preference by the Phycosiphon/Chondrites-producers related with their feeding strategies.-Burrows and feces of marine benthic animals are usually coated by mucus or mucus membrane (Bromley 1996), which contains abundant reactive organic matter (Lalonde et al 2010;Petrash et al 2011). Therefore, it is reasonable that Phymatoderma pellets, which have been interpreted as fecal pellets excreted by a surface deposit-feeding producer (Miller and Aalto 1998;Miller and Vokes 1998;Izumi 2012), were attractive for other benthos; thus Phymatoderma reworked by other ichnogenera such as Chondrites and Phycosiphon were recognized (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A common by-product of bioturbation is the introduction of labile organic matter, such as mucous secretions and fecal material, into the substrate (Steward et al, 1996;Hauck et al, 2008;Pak et al, 2010). Mucous secretions, for instance, represent ideal microenvironments for microbes since many of the burrows are lined with organic materials such as extracellular polysaccharides (i.e., microbial exopolymer secretions) and glycoprotein mucin (Konhauser andGingras, 2007, 2011;Lalonde et al, 2010;Petrash et al, 2011). For example, Gunnarsson et al (1999a) observed that elevated concentrations of a tetrachlorobiphenyl commonly occurred in the thin mucous layer covering the burrow linings of the polychaete Neries diversicolor compared to the surrounding bulk sediment.…”
Section: Impact Of Bioturbation On Substrate Biogeochemistrymentioning
confidence: 99%
“…This is because we ascribe the compositional differences observed in the isotopic distributions to reflect the different biogeochemical processes occurring within and adjacent to the burrows (Gingras et al, 2004;Konhauser andGingras, 2007, 2011;Rameil, 2008;Lalonde et al, 2010;Petrash et al, 2011;Corlett and Jones, 2012).…”
Section: Dolomitization Modelsmentioning
confidence: 99%